1994
DOI: 10.1182/blood.v83.1.176.bloodjournal831176
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between cyclosporin A and a monoclonal antibody to B7 in blocking alloantigen-induced T-cell activation

Abstract: Costimulatory signals are absolutely required for T-cell activation after T-cell receptor/major histocompatibility complex-peptide interaction. So far, the best-known candidate essential costimulatory signal is mediated by interaction of CD28 on T cells with B7 on antigen- presenting cells. Using an allogeneic B7+ Epstein-Barr virus- transformed B-cell line as stimulator, we found that addition of a monoclonal antibody (MoAb) to B7 that efficiently blocks B7-CD28 interaction only partially inhibited proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In vivo experiments in mice confirmed that CD80 costimulation was sufficient for activation of tumour antigen-specific CD8 T cells [14,15]. In previous studies, we and others demonstrated generation of CTL activity in cultures of human T cells by stimulation with anti-CD3 and CD80-transfected mouse cells [23,24] and with allogeneic B-cell lines [25]. More recent data in humans showed in vitro activation of isolated CD8 cells (proliferation and CTL generation) through costimulation by CD80 [26].…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…In vivo experiments in mice confirmed that CD80 costimulation was sufficient for activation of tumour antigen-specific CD8 T cells [14,15]. In previous studies, we and others demonstrated generation of CTL activity in cultures of human T cells by stimulation with anti-CD3 and CD80-transfected mouse cells [23,24] and with allogeneic B-cell lines [25]. More recent data in humans showed in vitro activation of isolated CD8 cells (proliferation and CTL generation) through costimulation by CD80 [26].…”
Section: Introductionmentioning
confidence: 63%
“…By bridging the effector CTL to the target cell FcR with anti-CD3 MoAb, this anti-CD3-redirected cytotoxicity system permits detection of CTL activity regardless of antigen specificity of the CTL [23]. In some experiments, CTL activity was also tested as the alloantigen-specific 4 h target cell lysis of the stimulator cell line [25,32]. One million targets were incubated for 1 h with 200…”
Section: Mixed Lymphocyte Reactions (Mlr) T Cells or Isolated Cd4mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, van Gool and colleagues have shown that the combination of CsA and CTLA4-Ig blocked the generation of alloantigen-specific CTL precursors, whereas reactivity to a third-party stimulator remained intact (122), Non-responsiveness could be reversed by culture in IL-2, indicating that clonal deletion did not occur. The combination of an anti-B7 mAb with low-dose CsA synergistically blocked T-cell proliferation and IL-2 production in response to alloantigen expressed on EBV-transformed B-cell lines in pri-mary as well as secondary MLR cultures (123). In contrast, in a different ex vivo culture system in which the frequency of alloreactive precursor T lymphocytes are measured in response to host or third party stimulators.…”
Section: Overview Of T-cell Costimulation Blockade To Induce Tolerancementioning
confidence: 99%